Effectiveness of Islamic Law in Protecting The Rights of The Child - Amer Hadi Abdullah; Abdullah, Waleed Mohammed; Kazem Al-Bayati, Adnan Khalil; Husain Al-Obaidi, Bushra Salman; Khlaponina, Svitlana (AL-ISTINBATH : Jurnal Hukum Islam, 2025)
The article critically evaluates the success of Islamic Family Law in meeting its core goals of child protection and welfare, comparing its influence and execution to the CRC's worldwide standards. Islamic Family Law provides a comprehensive framework based on religious and cultural norms to protect children's rights. Despite its strong basic principles, Islamic Family Law's practical application and efficacy in safeguarding children's rights varies greatly among sociopolitical circumstances, echoing the issues experienced by the Convention on the Rights of the Child (CRC). A mixed-method approach was used, combining quantitative analyses of child welfare statistics from mostly Islamic nations with qualitative evaluations based on case studies, interviews with legal experts, and reviews of secondary literature. Key indices of child welfare and rights were monitored throughout time, with comparison studies showing the disparities in results across different national contexts. The statistics show that Islamic Family Law has resulted in major advances in child welfare in a number of nations, while the extent of application and success varies. The efficacy of these legislation is heavily determined by unique sociopolitical and economic circumstances. The incorporation of Islamic values has facilitated worldwide discourse and action, raised awareness and established a precedent for child safety. Islamic Family Law has made significant contributions to defining the agenda for children's rights in Islamic contexts, but its practical impact varies greatly. A personalized, context-specific strategy, together with ongoing monitoring and modification, is required to guarantee that its ideas are universally recognized and effectively applied.